Novel organic/inorganic hybrid flower-like structure of selenium nanoparticles stabilized by pullulan derivatives. (15th March 2018) - Nonsuwan, Punnida; Puthong, Songchan; Palaga, Tanapat; Muangsin, Nongnuj
Highlights: Novel hybrid flower like structure of FA-CP/SeNPs was unexpectingly prepared. Folic acid decorated cationic pullulan (FA-CP) was designed for stabilizing SeNPs. The proposed mechanism of FA-CP/SeNPs hybrid microflower was described. The factors that effected on shape and morphology of SeNPs was investigated. The flower like structure of FA-CP/SeNPs could be a candidate as anticancer drug template. Abstract: We proudly present the first organic/inorganic hybrid pullulan/SeNPs hybrid microflower material obtained using a simple and bio-inspired strategy. The chemical structures of pullulan, folic acid decorated cationic pullulan (FA-CP) were designed for stabilizing selenium nanoparticles (SeNPs). SeNPs stabilized by FA-CP hybrid microflowers were observed after the addition of a cysteine hydrochloride solution into the solution mixture of Na2 SeO3 and FA-CP. We suggested that the concentrations of cysteine and FA-CP were the key factors for the formation of flower-like structure. In addition, the formation mechanism of the microflowers was tentatively identified as anisotropic hierarchical growth. The microflowers exhibited effective drug adsorption with the loading capacity of 142.2 mg g −1 for doxorubicin which was three times higher than that for the doxorubicin-loaded spherical SeNPs and showed more potent activity against cancer cells while showing less toxicity against normal cells. These data demonstrated that the microflower-like FA-CP/SeNPs structure could be a candidate anticancer drug template in drug delivery systems.